The museum of the senses : experiencing art and collections - Classen, Constance, 1957- (Sensory studies series., 2017)
"Traditionally sight has been the only sense with a ticket to enter the museum. The same is true of histories of art, in which artworks are often presented as purely visual objects. The Museum of the Senses offers a sensory history of art and collections, revealing how people used to handle, smell and even taste artworks and artefacts. Topics range from the tactile power of relics to the sensuous allure of cabinets of curiosities, and from the feel of a Rembrandt to the scent of Monet's garden. The book concludes with a discussion of how contemporary museums are stimulating the senses through interactive and multimedia displays. Constance Classen, a leading authority on the cultural history of the senses, has produced a fascinating study of sensual and emotional responses to artefacts from the middle ages to the present. The Museum of the Senses is an important read for anyone interested in the history of art as well as for students and researchers in cultural studies and museum studies"--